This is Brilliant : CBT, NLP, Confidence, Memory Training, Interview Answers, Negotiations, Selling, Presentation & Networking /: CBT, NLP, Confidence, Memory Training, Interview Answers, Negotiations, Selling, Presentation & Networking. (2013) - Briers, Stephen; Molden, David; Hutchinson, Pat; Eggert, Max; McClement, Mike; Hancock, Jonathan; Hodgson, Susan; Peeling, Nic; Hall, Richard; D'Souza, Steven; Cassell, Jeremy; Bird, Tom
No abstract available